Psychosomatic and vasomotor symptom changes during transition to menopause - Augoulea, Areti; Moros, Michalis; Lykeridou, Aikaterini; Kaparos, George; Lyberi, Rallou; Panoulis, Konstantinos (Menopause Review/Przegląd Menopauzalny, 2019)
Menopause is the condition in which the gradual decline in ovarian function finally leads to the permanent cessation of menstruation. Oestrogen deficiency may cause early symptoms during the menopausal transition and late symptoms after menopause. Menopause is a normal period of life. During this period, women need adaptation to new biological, social, and psychological parameters. Vasomotor symptoms are among the most common menopausal symptoms. Menopause per se is not correlated with specific psychiatric disorders, but data suggest that perimenopausal women are more likely to develop depressive disorders even without a previous history. Vasomotor symptoms are correlated with mood and sleep disturbances, neuroticism, anxiety, decreased cognitive function, and stress. Personality traits, social, and other factors are also important mediators of vasomotor symptoms during the menopausal transition phase. This is a review based on the existing evidence concerning the correlation between psychosomatic and vasomotor symptoms of menopause during the menopausal transition period. Healthcare providers should take these correlations into consideration when planning the treatment of vasomotor symptoms. Vasomotor symptoms during menopause are associated with significant social costs. There are numerous traditional hormone therapy, and complementary and alternative therapy including over-the-counter treatments and dietary supplements for managing menopause-related vasomotor symptoms. Additional costs include follow-up physician visits, laboratory testing, management of adverse events, and loss of productivity at work. Social support and planning may help women to deal with menopausal symptoms and may reduce overall social costs during this transitional phase.